Jean Lurçat : tapisseries, céramiques, lithographies (1974)
Photograph of tapestry work depicting a cockerel Poster advertising art exhibition of Jean Lurçat's works, held at the Galerie L'Art et la Paix, Paris, 5-29 March, 1974. Printed by Guillard, Gourdon et Cie., Paris PO-0176